Phylogenomics for Chagas Disease Vectors of the Rhodnius Genus (Hemiptera, Triatominae): What We Learn From Mito-Nuclear Conflicts and Recommendations - Filée, Jonathan; Merle, Marie; Bastide, Héloïse; Mougel, Florence; Bérenger, Jean-Michel; Folly-Ramos, Elaine; Almeida, Carlos Eduardo; Harry, Myriam (Frontiers in Ecology and Evolution, 2022)
We provide in this study a very large DNA dataset on Rhodnius species including 36 samples representing 16 valid species of Rhodnius sequenced with the Illumina technology. Using phylogenomics including 13 mitochondrial Protein Coding Genes (11.1 kb), partial nuclear rDNA (5.3 kb) and 51 nuclear Protein Coding Genes (36.5 kb), we resolve sticking points in the Rhodnius phylogeny. At species specific level, we assess the status of R. montenegrensis and R. marabaensis but refute that of R. taquarussuensis to synonymize with R. neglectus and invite to revisit the status of R. milesi that is more likely R. nasutus. We proposed to define a robustus species complex that comprises the four close relative species: R. marabaensis, R. montenegrensis, R. prolixus and R. robustus. In the Rhodnius genus, we recommend considering 19 valid species on the 21 described and including the three Psammolestes species by synonymizing Psammolestes and Rhodnius genus, which raises to 22 the number of species of the Rhodnius genus. At the Rhodnius group level, molecular data consistently supports the clustering of the pictipes and pallescens groups, more related to each other than they are to the prolixus group. Moreover, comparing mitochondrial and nuclear tree topologies, our results demonstrated that various introgression events occurred in all the three Rhodnius groups, in laboratory strains but also in wild samples. We demonstrated that introgressions occurred frequently in the prolixus group, invloving the close related species of the robustus complex but also the pairwise R. nasutus and R. neglectus. A genome wide analysis highlighted an old introgression between R. stali and R. brethesi and suggested a complex gene flow between R. colombiensis, R. pallescens and R. ecuadoriensis. The molecular data supports also a sylvatic distribution of R. prolixus in Brazil (Pará state) and the monophyly of R. robustus. As we detected extensive introgression events, we strongly recommend performing separate mitochondrial and nuclear phylogenies to take advantages of mito-nuclear conflicts in order to have a comprehensive evolutionary vision of this genus.